The neighborhood dimension at the crossroads of communication, city and public space. An ethnographic view of the contemporary urban subjectivation - Álvarez-Pedrosian, Eduardo (2018)
We propose the neighborhood dimension as a key for understanding urban phenomena in relation to its inhabitants’ practices, trying at the same time to give rise to the heterogeneity and connection of perspectives and experiences. In the introduction, we delineate the proposal’s scope, its relationship with communication, the city and the public space. Then, we focus on urban communication as a universe of mediations that inevitably express and thus produce subjectivity, and on ethnographic cases where intentional and involuntary dynamics can be observed in their effects. Later, we problematize the distinction between neighborhood and urban area, also based on ethnographic cases, to affirm a compositional perspective of the territories, according to the multiplicity of elements and their relative scales. Finally, we conclude by taking up the problematization of the public space and formulating wider considerations about similar spheres in other senses and practices.